Van der Waals Heterostructures: Type‐I Energy Level Alignment at the PTCDA—Monolayer MoS2 Interface Promotes Resonance Energy Transfer and Luminescence Enhancement (Adv. Sci. 12/2021). Issue 12 (24th June 2021) - Park, Soohyung; Mutz, Niklas; Kovalenko, Sergey A.; Schultz, Thorsten; Shin, Dongguen; Aljarb, Areej; Li, Lain‐Jong; Tung, Vincent; Amsalem, Patrick; List‐Kratochvil, Emil J. W.; Stähler, Julia; Xu, Xiaomin; et al.
Abstract : In article number 2100215, Soohyung Park, Sylke Blumstengel, Norbert Koch, and co‐workers demonstrate a key mechanism for opto‐electronic properties enhancement of an organic/inorganic van der Waals semiconductor heterostructure in the 2D limit. A straddling type‐I energy level alignment enables sub‐picosecond resonance energy transfer from organic molecules to a 2D inorganic semiconductor monolayer, with enhanced luminescence yield from the inorganic component.